2022
DOI: 10.1128/msystems.01491-21
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Adaptive Mechanisms of Extreme Acidophiles Based on Quorum Sensing/Quenching-Related Proteins

Abstract: Understanding cell-cell communication QS is highly relevant for comprehending the regulatory and adaptive mechanisms among acidophiles in extremely acidic ecosystems. Previous studies focused on the existence and functionality of a single QS system in several acidophilic strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…For example, some biofilm bacteria can produce QS-dependent enzymes that modify or degrade antimicrobial agents, reducing their effectiveness. The QS system is divided into four types, each using different signal molecules, including N-Acyl homoserine lactones (AHLs), such as autoinducer-2 (AI-2), and diffusible signaling factor (DSF) (Huang et al, 2022).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…For example, some biofilm bacteria can produce QS-dependent enzymes that modify or degrade antimicrobial agents, reducing their effectiveness. The QS system is divided into four types, each using different signal molecules, including N-Acyl homoserine lactones (AHLs), such as autoinducer-2 (AI-2), and diffusible signaling factor (DSF) (Huang et al, 2022).…”
Section: Quorum Sensingmentioning
confidence: 99%
“…A comprehensive QS database containing QS proteins described as involved in QS and QQ were downloaded using the application programming interface (https://rest.kegg.jp/). The QS gene sequences from the Kyoto Encyclopedia of Genes and Genomes (KEGG) database (KO:02024) and references related to QS systems were used as the basic data [17,34]. The genes involved in the synthesis, sensing, quenching, and transport of signal molecules were selected, and all amino acid sequences from the selected KEGG Orthologs (KOs) were retrieved (accessed in January 2023).…”
Section: Quorum Sensing Databasementioning
confidence: 99%
“…In addition to AHLs, acidophiles have enzyme systems encoding second messenger cyclic di-guanosine (c-di-GMP) that assist in regulating the QS system [ 41 ]. Huang et al revealed the presence of AHL, autoinducer-3, DSF, and AHL-degrading enzymes by annotating the genome of 83 species of acidophiles [ 42 ]. Bioinformatics prediction and laboratory experiments have identified the QS system in acidophiles.…”
Section: Introductionmentioning
confidence: 99%